Colombian consumers' outshopping of apparel in the U.S. Issue 2 (15th March 2018) - Ceballos, Lina M.; Jin, Byoungho; Ortega, Ana M.
Abstract: Outshopping is defined as purchasing goods outside of consumers' trading areas. Despite threatening local economies, outshopping generates opportunities for the new trading areas in which it occurs. Studies on outshopping have reported contradictory results and academics suggest further research, especially in relation to consumers' micro-level characteristics. Moreover, few studies have focused on the U.S. as the trading area and apparel as the traded product. Based on the theory of reasoned action, this quantitative study explores how attitudes toward international outshopping and subjective norm influence purchase intention of apparel goods among international outshoppers in the U.S. by focusing on four characteristics of international outshoppers – self-control in terms of spending, the desire for unique products, age, and gender – as antecedents of attitudes toward outshopping. Colombian consumers (South America) were chosen as respondents because market reports indicate that the U.S. is their top favorite international tourist destination. Findings suggest that more positive attitudes toward outshopping apparel in the U.S. were found among female consumers with higher self-control over their expenditures. Respondents were also influenced by the opinion of others; while age and desire for unique products were found non-significant. By understanding international outshoppers, marketers can develop unique market strategies for attracting global consumers.